Interrogating the plasma proteome of repetitive head impact exposure and chronic traumatic encephalopathy - Rowan Saloner; Kaitlin B. Casaletto; Sruti Rayaprolu; Louisa Cornelis; Paramita Chakrabarty; Jose F. Abisambra; Salvatore Spina; Lea T. Grinberg; William W. Seeley; Bruce L. Miller; Joel H. Kramer; Gil D. Rabinovici; et al. (Molecular Neurodegeneration)
Abstract Background Exposure to repetitive head impacts (RHI) is associated with increased risk for chronic traumatic encephalopathy (CTE), a neurodegenerative tauopathy, and other neuropathological changes. Biological drivers of RHI-related neurodegeneration are not well understood. We interrogated the plasma proteome in aging adults with prior RHI compared to healthy controls (CTL) and individuals with Alzheimer’s disease (AD), including a subset characterized neuropathologically at autopsy. Methods Proximity extension assay (Olink Explore®) quantified 2,779 plasma proteins in 22 RHI patients (all AD-biomarker negative), 39 biomarker-confirmed AD, and 44 CTL. A subset of participants went to autopsy (N = 16) allowing for comparisons of the antemortem plasma proteome between autopsy-confirmed CTE + (N = 7) and CTE- (N = 9). Differential abundance and co-expression network analyses identified plasma proteomic signatures of RHI, which were functionally annotated using gene ontology and cell type enrichment analysis. Nonparametric correlations examined plasma proteomic associations with orthogonally-measured plasma biomarkers, global cognitive function, and semi-quantitative ratings of neuropathology burden at autopsy. Results Differential abundance analysis revealed 434 increased (vs. 6 decreased) proteins in RHI vs. CTL and 193 increased (vs. 14 decreased) in RHI vs. AD. Network analysis identified 9 protein co-expression modules (M1-M9), of which 7 were elevated in RHI compared to AD or CTL. Modules with increased abundance in RHI were enriched for mitochondrial/metabolic, cell division, and immunovascular (e.g., cell adhesion, TNF-signaling) processes. RHI-related modules exhibited strong and selective correlations with immunoassay-based plasma IL-6 in RHI cases, including the M2 TNF-signaling/cell adhesion module which harbored proteins that strongly tracked with cognitive function. RHI-related plasma protein signatures were similar in the subset of participants with autopsy-confirmed CTE, including immune and metabolic modules that positively correlated with medial temporal lobe tau and TDP-43 burden. Conclusions Molecular pathways in plasma most consistently implicated in RHI were tied to immune response, mitochondrial function, and cell metabolism. RHI-related proteomic signatures tracked with antemortem cognitive severity and postmortem neuropathological burden, providing converging evidence for their role in disease progression. Differentially abundant proteins and co-expression modules in RHI may inform mechanisms linking RHI to increased dementia risk, thus guiding diagnostic biomarker and therapeutic development for at-risk populations.